Divergent Mechanisms Activating RAS and Small GTPases Through Post-translational Modification - Osaka, Natsuki; Hirota, Yoshihisa; Ito, Doshun; Ikeda, Yoshiki; Kamata, Ryo; Fujii, Yuki; Chirasani, Venkat R.; Campbell, Sharon L.; Takeuchi, Koh; Senda, Toshiya; Sasaki, Atsuo T. (Frontiers in Molecular Biosciences, 2021)
RAS is a founding member of the RAS superfamily of GTPases. These small 21 kDa proteins function as molecular switches to initialize signaling cascades involved in various cellular processes, including gene expression, cell growth, and differentiation. RAS is activated by GTP loading and deactivated upon GTP hydrolysis to GDP. Guanine nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs) accelerate GTP loading and hydrolysis, respectively. These accessory proteins play a fundamental role in regulating activities of RAS superfamily small GTPase via a conserved guanine binding (G)-domain, which consists of five G motifs. The Switch regions lie within or proximal to the G2 and G3 motifs, and undergo dynamic conformational changes between the GDP-bound “OFF” state and GTP-bound “ON” state. They play an important role in the recognition of regulatory factors (GEFs and GAPs) and effectors. The G4 and G5 motifs are the focus of the present work and lie outside Switch regions. These motifs are responsible for the recognition of the guanine moiety in GTP and GDP, and contain residues that undergo post-translational modifications that underlie new mechanisms of RAS regulation. Post-translational modification within the G4 and G5 motifs activates RAS by populating the GTP-bound “ON” state, either through enhancement of intrinsic guanine nucleotide exchange or impairing GAP-mediated down-regulation. Here, we provide a comprehensive review of post-translational modifications in the RAS G4 and G5 motifs, and describe the role of these modifications in RAS activation as well as potential applications for cancer therapy.